CITOGEN?TICA MOLECULAR EM ESP?CIES DA FAM?LIA PARODONTIDAE (PISCES; CHARACIFORMES) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
In this study, the fraction of the heterochromatin of the Apareiodon sp. chromosome W was isolated by microdissection with subsequent amplification by DOP-PCR. The sequences obtained were used in the procedure of the fluorescence in situ hybridization in Parodontidae species chromosomes. This probe was named WAp. Then, with this marker and others available, the study presented a molecular cytogenetic analysis in Parodontidae species present in different Brazilian hydrographic basin. The species analyzed were: Apareiodon sp., A. ibitiensis, A. vladii, A. piracicabae, A. vittatus, A. affinis, P. hilarii, P. moreirai, P. nasus and P. pongoensis. The results reveal closeness of the location of 18S rDNA marker found in Parodon species compared to the sister group Anostomidae. Still, it has been viewed a high identity chromosome pair bearing the rDNA 5S sites in all Parodontidae studied. Mapping of repetitive DNAs WAp and pPh2004 by fluorescence in situ hybridization in chromosomes of some species of Parodontidae permitted deduce the origin and differentiation of sex chromosome system ZZ/ZW from a inversion allocating proximal region WAp sites of a chromosome metacentric pair. These results allowed inferring that the sex chromosome system multiple ZZ/ZW1W2 of A. affinis can originate from one system ZW similar to that found in ancient populations of species P. hilarii. Thus, this work contributes to the understanding of development and diversification of the genome of some species of Parodontidae, mainly to the comprehension of the origin and sex chromosome differentiation.
Keywords: Parodontidae; Dispers?o de sitio rDNA; evolu??o cariotipica; microdissec??o do cromossomoW; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR